Exploring Search Techniques and Future Trends in Web Mining - Krishna, Tiruveedula Gopi; Sreenivas, Nune; Urgessa, Teklu; Abetu, Megersa Daraje; Aga, Melkamu Abetu; Mahboub, Mohamed Abdeldaiem (Mathematics and Computer Science: Research Updates Vol. 2, 2025)
Web mining is a very essential process for the acquisition of useful information from the big and frequently changing information on the Web. This chapter focuses on the presentation of various methods of searching in web mining stressing the role of searching methods for effective data search in web space. The three broad techniques are discussed as keyword-based search, structure-based search, and semantic search, with an emphasis on the methods of each, their reliability, and their weaknesses. The chapter also provides an account of the developments in the search methods contributing to increasing understanding of the technological factors that have influenced web mining over time. Besides, it defines current trends and future developments to broaden the scope of understanding, such as inspirations drawn from machine learning and artificial intelligence to improve search potential. Providing an introduction to many of the methods and tools presented in this book chapter. This chapter highlights the importance of employing expert-level search methods for making better decisions with data and prompting the field of Web mining forward.